The use of augmented reality applied in teaching (Research, Society and Development, 2019)
Increasing the student's participation in the classroom so that it becomes more productive and that the classes perform more is a challenge for every teacher. In this context, our general objective is to exemplify how the use of Augmented Reality can help in teaching, and for this it was necessary: to present the advantages of the use of Augmented Reality (AR); to exemplify how RA is used in the current media ecosystem; and comment on what is needed to develop didactic materials with the use of three-dimensional technology. The methodology used was exploratory and descriptive, followed by an experiment with a class of students showing the use of this tool as a complement to the explanation of the contents in the classroom. The results show that the augmented reality can transform the use of the cell phone in the classroom, making it a learning tool and we can see that the use of the mobile phone and the AR can be an interesting allies in the student's learning, it is enough to understand about costs and benefits of its use.